Analisis kelayakan bisnis: UMKM kerupuk singkong nusantara putra 2 “Ibu Hj Khotimah” - Shalsabila, Izzatunnisa Habiba; Salsabiila, Salsabiila; Agustina, Ananda; Solekah, Nihayatu Aslamatis (Maliki Interdisciplinary Journal, 2024)
Kerupuk Singkong Nusantara Putra 2 “Ibu Hj Khotimah” is a small and medium-sized enterprise (SME) located in Dusun Sekar Putih, Desa Pendem, Kota Batu, and has been in operation since 2015. Kerupuk Singkong Bu Khotimah is an SME in the food and beverage (F&B) industry and has the legal business permit, known as NIB (Nomor Induk Berusaha), and is also halal certified. The marketing aspect is through direct selling and currently uses WhatsApp media for digital promotion. In terms of technology, modern equipment or dough cutting tools are used, which will later become crackers. This SME has approximately 10 employees. The Kerupuk Singkong Bu Khotimah SME also has a solution for disposing of cassava skin waste, which usually reaches 60 kg, by selling it back as cattle feed.